2010
DOI: 10.1371/journal.pone.0012221
|View full text |Cite|
|
Sign up to set email alerts
|

Expansion of Cord Blood CD34+ Cells in Presence of zVADfmk and zLLYfmk Improved Their In Vitro Functionality and In Vivo Engraftment in NOD/SCID Mouse

Abstract: BackgroundCord blood (CB) is a promising source for hematopoietic stem cell transplantations. The limitation of cell dose associated with this source has prompted the ex vivo expansion of hematopoietic stem and progenitor cells (HSPCs). However, the expansion procedure is known to exhaust the stem cell pool causing cellular defects that promote apoptosis and disrupt homing to the bone marrow. The role of apoptotic machinery in the regulation of stem cell compartment has been speculated in mouse hematopoietic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…We have earlier reported that the addition of anti-apoptotic agents resulted in increased expansion efficiency of suspension cultures of UCB CD34 + cells [ 17 ]. Since higher levels of apoptosis were detected in the C-MSCs:CD34 + co-cultures, we checked if this system could be made equivalent to the P-MSCs co-cultures by the addition of anti-apoptotic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…We have earlier reported that the addition of anti-apoptotic agents resulted in increased expansion efficiency of suspension cultures of UCB CD34 + cells [ 17 ]. Since higher levels of apoptosis were detected in the C-MSCs:CD34 + co-cultures, we checked if this system could be made equivalent to the P-MSCs co-cultures by the addition of anti-apoptotic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we identified a distinctive aspect of apoptosis (negative regulation) that influenced the expansion of CD34 + cells. Our study revealed that the cell-permeable inhibitors of caspase and calpain proteases, augmented the expansion and long-term engraftment of cord blood CD34 + cells [13]. We speculated that the mechanism behind the sustained engraftment might lie in the ability of the inhibitors to influence the migratory and adhesive interactions of these cells in vitro.…”
Section: Introductionmentioning
confidence: 73%
“…This led to the study of caspase inhibitors as cryopreservatives. The initial encouraging results on cell cultures (Heng, Clement, & T. Cao, 2007;Stroh et al, 2002), were recently supported by in vivo experiments (Sangeetha, Kale, & Limaye, 2010). Other cryo-preservative additives, such as α tocopherol (Neunert et al, 2009;E J Woods et al, 2000), are under investigation and may be of future interest.…”
Section: Alternatives To Standard Dmsomentioning
confidence: 93%
“…Whilst platelet recovery and the median amount of blood products transfused did not differ in between the two groups, the patients obtaining cell concentrates, cryopreserved with the DMSO/HES combination obtained neutrophil recovery in average one day earlier and needed one day less antibiotic administration(p=0.04) (Rowley et al, 2003). Unfortunately hematopoietic and other stem cells, particularly human embryonic stem cells, undergo apoptotic transformation during the cryopreservation process (Sangeetha, Kale, & Limaye, 2010;Stroh et al, 2002). This led to the study of caspase inhibitors as cryopreservatives.…”
Section: Alternatives To Standard Dmsomentioning
confidence: 99%